Pepblock Builder VR – An Open-Source Tool for Gaming-Based Bio-Edutainment in Interactive Protein Design - Yallapragada, Venkata V. B.; Xu, Tianshu; Walker, Sidney P.; Tabirca, Sabin; Tangney, Mark (Frontiers in Bioengineering and Biotechnology, 2021)
Proteins mediate and perform various fundamental functions of life. This versatility of protein function is an attribute of its 3D structure. In recent years, our understanding of protein 3D structure has been complemented with advances in computational and mathematical tools for protein modeling and protein design. 3D molecular visualisation is an essential part in every protein design and protein modeling workflow. Over the years, stand-alone and web-based molecular visualisation tools have been used to emulate three-dimensional view on computers. The advent of virtual reality provided the scope for immersive control of molecular visualisation. While these technologies have significantly improved our insights into protein modeling, designing new proteins with a defined function remains a complicated process. Current tools to design proteins lack user-interactivity and demand high computational skills. In this work, we present, Pepblock Builder VR , a gaming-based molecular visualisation tool for bio-edutainment and understanding protein design. Simulating the concepts of protein design and incorporating gaming principles into molecular visualisation promotes effective game-based learning. Unlike traditional sequence based protein design and fragment based stitching, Pepblock Builder VR provides a building block style environment for complex structure building. This provides users a unique visual structure building experience. Furthermore, the inclusion of virtual reality to Pepblock Builder VR brings immersive learning and provides users with ‘being there’ experience in protein visualisation. Pepblock Builder VR works both as a standalone and VR based application and with a gamified user interface, Pepblock Builder VR aims to expand the horizons of scientific data generation to the masses.